2019
DOI: 10.1016/j.molp.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Module Controlling GA-Mediated Endosperm Cell Expansion Is Critical for Seed Germination in Arabidopsis

Abstract: A key component of seed germination is the interplay of mechanical forces governing embryo growth and the surrounding restraining endosperm tissue. Endosperm cell separation is therefore thought to play a critical role in the control of this developmental transition. Here we demonstrate that in Arabidopsis thaliana seeds, endosperm cell expansion is a key component of germination. Endosperm cells expand to accommodate embryo growth prior to germination. We show that this is an actively regulated process suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 65 publications
1
74
0
2
Order By: Relevance
“…These processes require that specific genes are expressed in specific subsets of cells, under the control of distinct genome regulatory programs (Stamm et al , ; Topham et al , ). Transcription factors have an important role in regulating gene expression spatially and temporally during germination (Bassel et al , ; Narsai et al , ; Sánchez‐Montesino et al , ). However, the details of which transcription factors act as regulators when and where are poorly understood, particularly in crop species (Betts et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…These processes require that specific genes are expressed in specific subsets of cells, under the control of distinct genome regulatory programs (Stamm et al , ; Topham et al , ). Transcription factors have an important role in regulating gene expression spatially and temporally during germination (Bassel et al , ; Narsai et al , ; Sánchez‐Montesino et al , ). However, the details of which transcription factors act as regulators when and where are poorly understood, particularly in crop species (Betts et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mechanical force adjustments by expansion of endosperm cells surrounding the elongating embryo prior to radicle emergence as critical for successful germination has been identified in Arabidopsis thaliana (Bassel et al, 2014;Sá nchez-Montesino et al, 2018;Stamm et al, 2017). Using cell surface area measurements by confocal imaging and 3D geometry reconstruction, Sá nchez-Montesino et al (2018) identified that the region of the endosperm surrounding the lower hypocotyl and the radicle exhibit the highest expansion rates in imbibed seeds.…”
Section: Biophysical Forces Associated With Seed Germination Are Regumentioning
confidence: 99%
“…These results highlight the importance of biophysical forces in regulating seed germination. Subsequently, NAC transcription factors NAC25 and NAC1-like (NAC1L) were identified as activators of EXPANSIN2 (EXPA2) expression that regulates the GAmediated endosperm cell expansion during seed germination (Sá nchez-Montesino et al, 2018). The DELLA protein RGL2 sequesters NAC25 upon interaction and represses the activation of EXPA2 (Sá nchez-Montesino et al, 2018) under a low GA environment, which is an excellent example of negative regulation of target gene expression by DELLA protein (Figure 1).…”
Section: Biophysical Forces Associated With Seed Germination Are Regumentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously established that phototropism is the balance between the differential growth response and the hypocotyl growth inhibition in a fluence rate‐dependent fashion (Whippo and Hangarter ). While GAs relieve the growth inhibition by promoting DELLAs degradation via the ubiquitin‐proteasome pathway in a dose‐dependent manner (Sasaki et al ; Fu et al ; Hauvermale et al ; Gomez et al ; Sanchez‐Montesino et al ), sucrose stabilize DELLA proteins and inhibits growth (Li et al ). We analyzed the effect of GAs on phototropism and found that the phototropic response of the phot1 phot2 mutant was slightly rescued by GA 3 (Figure A, B) and, in contrast, the impaired phototropic response phenotype of the phot1 phot2 cry1 cry2 quadruple mutant was not affected by GAs (Figure A, B), similar to the effects of depleting sucrose from the medium (Figures , 2).…”
Section: Discussionmentioning
confidence: 99%